Firefighter Public Information Officers’ Communication Effectiveness with the Media During the 1998 Florida Wildfires - Ricky Telg; Becky Raulerson (Journal of Applied Communications, 1999)
The purpose of this study was to assess how firefighter public information officers perceived their effectiveness as they communicated with the media during the 1998 Florida wildfires. A questionnaire was mailed to every member (99) of the Public Information Officer Section of the Florida Fire Chiefs’ Association in spring 1999; 49 responded. A separate survey was sent to 50 newswire agencies, newspapers, and television and radio stations that were in areas impacted by the Florida wildfires to find out reporters’ perceptions of public information officers’ communication effectiveness. Results from the study include the following: public information officers (PIOs) said having reporters present at a wildfire scene did not affect how command centers fought the fires; most PIOs believed they did an above-average job communicating effectively with the media; reporters gave PIOs good marks for communication effectiveness; and PIOs noted that although most had considerable communication training and/or experience, they would have liked more comprehensive training before the wildfire outbreak.